Impact of the COVID-19 pandemic on the sexual and reproductive health of adolescents in Alberta, Canada - Salima Meherali; Amyna Ismail Rehmani; Mariam Ahmad; Bisi Adewale; Samar Kauser; Simone Lebeuf; James Benoit; Shannon D. Scott (BMC, 2023)
Abstract Purpose The COVID-19 pandemic led to major service disruptions in the healthcare sector, especially regarding sexual and reproductive health services. However, the impact of the pandemic on Canadian adolescents is relatively unknown. This study aimed to investigate the impacts of the COVID-19 pandemic and associated public health measures on the sexual and reproductive health (SRH) of adolescents in Alberta, Canada. Methods A qualitative study using an interpretive description (ID) approach and community-based participatory research principles was conducted to capture the subjective experience and perceptions of adolescents and service providers. With the collaboration of the Adolescent Advisory Group and community partners, 18 adolescents and 15 service providers were recruited for the study through purposive sampling. Findings from the qualitative interviews were analyzed using thematic analysis. Results Three major themes emerged from the analysis: (1) COVID-19 SRH experience, (2) barriers to SRH, and (3) adolescent SRH strategies. Our findings highlight numerous barriers and challenges that prevented adolescents from accessing SRH education, products, and services. Conclusion The COVID-19 pandemic had a profound impact on the SRH and the well-being of adolescents. Our study reflects the need for diverse SRH strategies to maintain continued access to SRH resources during disruptive events, such as the pandemic.